The clinical method as a diagnosis method. A critique to a standing conception. - Luis Alberto Corona Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
The importance of the clinical method in the assistance practice is out of question. In this article, through a systemic point of view and from the medical assistance perspective, it is analyzed how, historically conditioned, the clinical method has been considered up to this moment as a method for medical diagnosis, which limits the fulfillment of the general objective of the medical attention process. That's why we consider the actual theory an insufficiently developed model for, as a teaching content in the Medicine career; contribute to the learning of the medical attention process.